Remarks on the issue of urban agglomerations in the Diocese of Thraciae (4th–6th centuries). State of research and prospects - Biernacki, Andrzej (Balcanica Posnaniensia. Acta et studia, 1990)
The article concerns the issue of urban agglomerations in the diocese of Thraciae in the 4th–6th centuries. The research problem includes the state of research on urban settlement and the need for its methodological organization. The aim of the work is to indicate directions for further research and to propose a comprehensive approach. The author applies theoretical analysis and a review of previous studies. The most important results indicate that research on settlement should integrate various disciplines: archaeology, geography, history, and urban studies. The development of urban agglomerations should be analyzed on three levels: province, microregion, and topographical unit. The author also emphasizes the importance of environmental, economic, and social factors in shaping urban structures. The conclusion is the necessity of interdisciplinary and synthetic research.